Aníbal Pinto de Castro, in memoriam, a year after his death - Martel, Juan Manuel (Revista de Filología Románica, 2012)
The evocation of some aspects of the personality and extended philological work of Aníbal Pinto de Castro, professor of "Literatura portuguesa" of the Universidade de Coimbra while he was related to Universidad Complutense de Madrid.
Keywords: Coimbra University; Madrid University; Romance Philology; Portuguese language.